2023
DOI: 10.1039/d3fo00355h
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glucolipid metabolism and gut microbiota by green and black teas in hyperglycemic mice

Abstract: High-sugar and -fat diets (HSFD) have become a primary risk factor for diabetes, and diet intervention shows a substantial effect on the prevention and management of hyperglycemia. In this study,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…On the other hand, black tea demonstrated the capacity to improve glucose uptake and metabolism, thereby reducing postprandial blood glucose levels. Furthermore, it had a positive impact on the composition of intestinal microorganisms by increasing the abundance of beneficial bacteria in the body [45]. This study revealed that two Japanese green tea varieties, Indo and Cha Chuukanbohon Nou 6, have potent DPP-4 inhibitory activity.…”
Section: Effect Of Tea Products With Different Fermentation Degrees O...mentioning
confidence: 78%
See 2 more Smart Citations
“…On the other hand, black tea demonstrated the capacity to improve glucose uptake and metabolism, thereby reducing postprandial blood glucose levels. Furthermore, it had a positive impact on the composition of intestinal microorganisms by increasing the abundance of beneficial bacteria in the body [45]. This study revealed that two Japanese green tea varieties, Indo and Cha Chuukanbohon Nou 6, have potent DPP-4 inhibitory activity.…”
Section: Effect Of Tea Products With Different Fermentation Degrees O...mentioning
confidence: 78%
“…Simultaneously, it led to a reduction in the levels of Clostridium and Bacteroides. Importantly, deeply fermented black tea exhibited a more significant effect in this context [45]. Additionally, administering extracts of both conventional black tea and selenium-enriched black tea to hyperglycemic mice can modify the composition of intestinal microorganisms.…”
Section: Regulation Of Gut Microbiotamentioning
confidence: 95%
See 1 more Smart Citation
“…PI3K further activates Akt, which can further activate downstream proteins, promote intracellular energy metabolism, increase glucose consumption in the body, promote fatty acid oxidation metabolism, and inhibit liver lipid synthesis. The activation of IRS-1 protein can also promote insulin activation, regulate the body’s gluconeogenesis process, and inhibit the conversion of nonsugar substances into glucose in the body . As shown in Figure D, compound 75 significantly upregulated the expression of IRS-1, PI3K, and Akt phosphorylation in HepG2 cells after administration, suggesting that the hypoglycemic mechanism of 75 may be related to the regulation of the IRS-1/PI3K/Akt signaling pathway.…”
Section: Resultsmentioning
confidence: 94%
“…Enormous evidence has shown that tea and its contained bioactive compounds have positive effect on health, including inhibition of cancer cells ( 13 ), anti-inflammatory attributes ( 14 ), cardiovascular protection ( 15 ), enhancement of liver function ( 16 ), blood sugar regulation ( 17 , 18 ), neuroprotective qualities ( 19 ), promotion of skin health ( 20 , 21 ), and favorable effects on bone health ( 22 ), whereas their specific action mechanisms are still unclear. Recent research has underscored the gut microbiota may play a pivotal role in the health benefits of tea ( 23 , 24 ). For example, the application of tea polysaccharides conjugates (TPS) in Ulcerative colitis (UC) mice significantly altered the composition of the gut microbiome, contributing to the restoration of intestinal homeostasis ( 25 ).…”
Section: Introductionmentioning
confidence: 99%